Sexual and Gender Minorities and Risk Behaviours among University Students in Italy - Marco Fonzo (MDPI AG, 2021)
Sexual and gender minorities (SGM) may experience stigma, discrimination and show higher prevalence of behavioural risk factors than heterosexual counterparts. In Italy, the information on SGM is scarce and outdated. The present cross-sectional study aims to provide a more up-to-date estimate of the SGM proportion in young adults and to assess differences in the adoption of risk behaviours compared to their heterosexual counterparts. The study involved university students aged 18–25. Information on socio-demographic and behavioural characteristics were collected. The effect of sexual orientation on risk behaviours was assessed with a multinomial single-step logistic regression analysis. A total of 9988 participants were included. Overall, 518 students (5.2%) self-identified as SGM. While lesbians showed significantly higher odds of only non-regular use of protective barriers (AOR: 11.16), bisexuals showed higher odds for frequent drinking (AOR: 2.67), smoking (AOR: 1.85), multiple sexual partnerships (AOR: 1.78) and non-regular use of protective barriers (AOR: 1.90) compared with heterosexual women. Gay men showed higher odds of multiple sexual partnerships compared with heterosexual males (AOR: 5.52). SGM accounted for 5.2% of the sample, slightly more than the proportion found in the general population, but substantially in line with similarly aged populations abroad. Our findings confirm that unhealthy risk behaviours are more frequent among LGBTQ+, in particular among bisexual women. Rather than targeting specific subpopulations, our study aims to show the need for health promotion interventions that aim at the empowerment of all students regardless of sexual orientation, being aware that SGMs can benefit to a relatively greater extent.